2017
DOI: 10.1186/s12936-017-1892-y
|View full text |Cite
|
Sign up to set email alerts
|

Extremely low Plasmodium prevalence in wild plovers and coursers from Cape Verde and Madagascar

Abstract: BackgroundRelatively little is known about the prevalence of blood parasites in shorebirds, especially those breeding in the tropics. The prevalence of blood parasites of the genera Plasmodium, Haemoproteus and Leucocytozoon was assessed in blood samples from Kentish plovers and cream-coloured coursers in Cape Verde, and samples of Kittlitz’s plovers, Madagascar plovers and white-fronted plovers in Madagascar.ResultsOnly two of these samples were positive for Plasmodium: a Kittlitz’s plover was infected by a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Strong relationships between landscape use and the prevalence of blood parasites infecting birds have previously been shown (Fourcade et al., ; Patz et al., ), which may be due to the effect of landscape features on the vector community (Norris, ). For instance, the scarcity of suitable vectors has been identified as the most likely reason of the low prevalence or absence of Plasmodium in birds from marine and saline environments (Figuerola, ; Gutiérrez‐López et al., b; Martínez‐de la Puente et al., ; Mendes, Piersma, Lecoq, Spaans, & Ricklefs, ) and deserts (Merino, Barbosa, Moreno, & Potti, ). Indeed, environmental characteristics strongly determined the mosquito abundance and community composition in the study area (Ferraguti et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Strong relationships between landscape use and the prevalence of blood parasites infecting birds have previously been shown (Fourcade et al., ; Patz et al., ), which may be due to the effect of landscape features on the vector community (Norris, ). For instance, the scarcity of suitable vectors has been identified as the most likely reason of the low prevalence or absence of Plasmodium in birds from marine and saline environments (Figuerola, ; Gutiérrez‐López et al., b; Martínez‐de la Puente et al., ; Mendes, Piersma, Lecoq, Spaans, & Ricklefs, ) and deserts (Merino, Barbosa, Moreno, & Potti, ). Indeed, environmental characteristics strongly determined the mosquito abundance and community composition in the study area (Ferraguti et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…This prevalence is similar to the prevalence of 16.5–30 % reported in great snipes ( Halvarsson, 2016 ; Höglund et al, 2017 ). However, other studies reported lower parasite prevalence in other wader species ( Clark et al, 2016 ; Martínez-De La Puente et al, 2017 ; Mendes et al, 2005 ; Pardal et al, 2014 ). For example, a comparative analysis across 46 species of five continents using a global database revealed an average prevalence of 6.2 % for wader species ( Clark et al, 2016 ).…”
Section: Discussionmentioning
confidence: 75%
“…A final functional explanation for the absence of MHC‐based mate choice might be that larks in arid environments generally have very few parasites (Horrocks et al., 2012). Studies of avian malaria in the Cape Verde archipelago revealed extremely low prevalence: no single infection in 40 plovers and coursers (Charadriformes; Martínez‐de la Puente et al., 2017), and six out of 130 common kestrels Falco tinnunculus infected (Hille, Nash, & Krone, 2007), presumably largely due to a scarcity of vectors. There are no mosquitos on Raso, and we have not observed any otherwise frequently observed avian ectoparasites, such as feather lice (Insecta: Phthiraptera), on adults or in nests of the Raso lark (M. de L. Brooke, personal observation).…”
Section: Discussionmentioning
confidence: 99%